Halal Chocolate Purchase Intention And Compliance: Examining The Moderating Role Of Religiosity Among Malaysian Muslims - Wan Rasyidah Wan Nawang; Syadiyah Abdul Shukor; Amalina Mursidi; Anita Ismail (2026)
Indexed by MyCite